2020
DOI: 10.3390/ijms21165641
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Semaphorins in Metabolic Disorders

Abstract: Semaphorins are a family originally identified as axonal guidance molecules. They are also involved in tumor growth, angiogenesis, immune regulation, as well as other biological and pathological processes. Recent studies have shown that semaphorins play a role in metabolic diseases including obesity, adipose inflammation, and diabetic complications, including diabetic retinopathy, diabetic nephropathy, diabetic neuropathy, diabetic wound healing, and diabetic osteoporosis. Evidence provides mechanistic insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 136 publications
(158 reference statements)
0
18
0
Order By: Relevance
“…These conditions could account for the role of SEMA5A polymorphisms in HRQOL. Additionally, SEMA5A could play a role in chemotherapy-induced peripheral neuropathy (CIPN) given that it is important in the guidance of axons in the central and peripheral nervous system and also that semaphorins are involved in diabetic neuropathy [ 59 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…These conditions could account for the role of SEMA5A polymorphisms in HRQOL. Additionally, SEMA5A could play a role in chemotherapy-induced peripheral neuropathy (CIPN) given that it is important in the guidance of axons in the central and peripheral nervous system and also that semaphorins are involved in diabetic neuropathy [ 59 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that semaphorin signaling plays a pivotal role in various pathophysiological processes outside the nervous system [ 2 , 3 ]. Recent studies have focused on the functions of semaphorin signaling in immunometabolic regulation and disorders, such as obesity, diabetes, and atherosclerosis [ 4 6 ]. In addition, we recently found that Sema6D signaling induces lipid metabolic reprogramming that is indispensable for anti-inflammatory polarization of macrophages, thus highlighting an essential link between semaphorin signaling and lipid metabolism [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plexins are also receptors for semaphorins, a large family of proteins involved in various physiological processes 88 . Semaphorins are involved in a number of diabetic complications including diabetic retinopathy, nephropathy, and neuropathy, osteoporosis, and wound healing 89 . Interestingly, we observed significantly higher levels of CD72 in the SIDD subtype and as CD72 appears to mediate the function of semaphorins in some immune cells 90 , it may provide a potential functional link to PLXNB2.…”
Section: Discussionmentioning
confidence: 99%